Energy-Saving Construction Technologies and Operation and Maintenance Control of Ultra-Low Energy Building Based on Intelligent Control - Li Ge (Forest Chemicals Review, 1970)
In recent years, the ultra-low energy building technology has developed rapidly. Various provinces and cities have provided relevant policy support, and numerous technical index documents and normative are constantly revised and updated as required. Technological innovation has been made in ultra-low energy building renewal, design and manufacture of new materials and intelligent operation and maintenance to continuously promote the development of the industry. This paper aims to summarize the general technical measures and construction technology for the conservation of ultra-low energy building and put forward the technical scheme of intelligent control and intelligent operation and maintenance to provide technical support for the development of building energy conservation technology.